Online detection technology for SF6 decomposition products in electrical equipment: a review. Issue 6 (1st September 2018) - Fan, Xiaopeng; Li, Li; Zhou, Yongyan; Tang, Nian; Zou, Zhuanglei; Li, Xiaodian; Huang, Guojun; Liu, Mingzheng
Abstract : The decomposition component analysis method can be used to monitor and diagnose the insulation state of SF6 electrical equipment in power industry. Here, the authors firstly compared the advantages and disadvantages of various SF6 decomposition products detection methods and analysed their feasibility of online monitoring. Then the requirements of SF6 decomposition products online detecting technology according to the actual engineering needs were discussed. The SF6 decomposition products online detection system has been mainly introduced from the aspects of principle, structure, detection effect, and practicability. The research points and development tendency of SF6 decomposition products online detection system is forecasted.